Reflection on the online learning of Pancasila and Citizenship in an international class program - Elisabeth Rukmini; Pedy Artsanti; Arya Susila Nugraha (Universitas Negeri Yogyakarta, 2021)
The main problem of the Pancasila and Citizenship courses is the substance problem which is cognitive domains, and the problem of learning approaches. This research results from active collaboration between universities online with the Pancasila & Citizenship learning design for international class students of FTI UII. This research aims to explore the results of online learning Pancasila and Citizenship from student reflections. This goal is to be achieved by analyzing qualitative data on student reflections and analyzing the results of student evaluations of the five-step learning program